Early Breastfeeding Practices, Energy and Protein Intake, Risk of Stunting in Coastal Areas of Sampang Regency, East Java Province: A Cross-Sectional Study - Khomisah, Nuril Alfiatul; Hikmayani, Nur Hafidha; Probandari, Ari Natalia (Journal of Health and Nutrition Research, 2025)
Stunting remains a significant public health issue in Indonesia, particularly in coastal areas with limited access to nutrition and healthcare services. This study aims to identify early risk factors for stunting in children aged 12–59 months in the coastal areas of Sampang Regency, East Java. The study design employed a cross-sectional approach with a sample size of 250 children, selected randomly in proportion to the population. Data were collected through anthropometric measurements, structured questionnaires, and 24-hour food recalls. Analysis was performed using the chi-square test and simple logistic regression. The results showed a prevalence of stunting of 25,2%. Not getting breast milk in the first two days postpartum (OR=2,447), not getting exclusive breastfeeding for <6 months (OR=2,766), insufficient energy intake (OR=27,695), and insufficient protein intake, which showed the highest risk (OR=192,85), were associated with stunting (p<0,05). In contrast, early initiation of breastfeeding and continued breastfeeding at 12–23 months of age were not significantly associated with stunting. These findings underscore the importance of early nutritional practices and adequate intake of macronutrients, particularly protein, in efforts to prevent stunting. Focused nutritional interventions during the first 1,000 days of life need to be prioritized, including improving maternal education and the quality of children’s food intake.